Ecosystem services assessment of Beledanga oxbow lake in the Gangetic plains: pathways to sustainable conservation - Ekka, Anjana; Das, Basanta Kumar; Roy, Aparna; Pandit, Arun; Swain, Prajna Ritambhara; Lianthuamluaia, Lianthuamluaia; Chanu, Thangjam Nirupada; Parida, Pranaya Kumar; Debroy, Piyashi; Bhattacharya, Shreya; Chakraborty, Sangeeta; Mondal, Kausik (Frontiers in Freshwater Science, 2024)
Oxbow lakes, formed from abandoned river meanders, are unique wetlands that play a crucial role in supporting aquatic biodiversity and sustaining local communities through their ecosystem services. This study focuses on the Beledanga oxbow lake, highlighting its ecosystem services and the critical role of hydrological connectivity with the adjacent river for maintaining ecological functionality and sustainability. Using the Millennium Ecosystem Assessment framework, the study assessed provisioning, regulating, cultural, and supporting services through field surveys, stakeholder consultations, and secondary data analysis. Results show that the lake provides essential provisioning services, such as fisheries and irrigation, which support local food security and income generation. It also plays a role in regulating services like water management and carbon sequestration, while its biodiversity underpins vital ecological functions, including nutrient cycling and habitat provision. However, challenges such as seasonal water scarcity and macrophyte infestation threaten the lake's productivity and connectivity with the river. The study emphasizes the need for collaborative efforts involving local stakeholders to devise water management strategies and remove macrophytes, utilizing government initiatives like the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) for funding. Additionally, the establishment of robust monitoring systems for sustainable fisheries management and incentive programs for conservation efforts are recommended. The research highlights the importance of hydrological connectivity in sustaining the lake's ecosystem services and enhancing biodiversity. By integrating local knowledge and stakeholder engagement, this study provides valuable insights into the sustainable management of oxbow lakes and highlights the broader significance of river-oxbow lake connectivity in wetland conservation efforts. The findings also have implications for broader wetland conservation policies in similar ecosystems.